Digital Resonance: Enhancing Pronunciation through Tech-Infused Teaching Strategy - Halimah Halimah; Reza Rahman Hakim; Asep Saepuloh (MultiTech Publisher, 2023)
The intention of this research is to discover the implementation of Cake in teaching of pronunciation and to uncover the students’ perception toward the use of Cake in teaching of pronunciation. This research applied qualitative descriptive method. The study was conducted at a private vocational school in Cianjur West Java Indonesia in the academic year 2021. The participants consisted of second grade of banking major at the ages between 15-17. Two of them were male and ten were female. This research collected the data through observation and a forced-choice questionnaire format where the participants were asked to choose one of the available selections (Yes or No). As the data were collected, the writer analyzed them. There were six steps in analyzing the observation as well as the questionnaire: (1) preparing the data to be analyzed, (2) reading or viewing all data, (3) coding the data, (4) generalizing the code, (5) creating tables based on the data code, and (6) interpret the data code. Over the observation the writers found a new formula on implementing Cake in helping students’ pronunciation accuracy. This formula then is called MRCP with drilling as the teaching strategy. The results of questionnaire show that Cake was new for the student. It has many features that support students in learning pronunciation. The students were also happy learning using Cake and they felt more confident to speak English after learning using Cake.